New insights into sprint biomechanics and determinants of elite 100m performance - Miorin, J.-B.; Edouard, P.; Samozino, P. (New Studies in Athletics, 2013)
ABSTRACT The laws of mechanics dictate that accelerating body mass in the forward direction requires sprinters to produce force, but also to apply it to the ground in order to generate as much horizontally-oriented ground reaction force (GRF) as possible. Although theoretically obvious, this principle has hitherto not been confirmed by experimental measurements, especially in top-level athletes. The authors used a motorised instrumented treadmill and other techniques to study the relationships between 100m performance and running mechanics, with a specific focus on GRF (resultant, vertical and horizontal components) production and application, in sport science students, national-class sprinters and a world-class performer. They found that the amount of horizontal GRF produced during maximal treadmill sprints is highly correlated to 100m performance, and that how the resultant GRF is applied also correlates to 100m performance. Specifically, they show the importance of horizontally-oriented force versus vertically-oriented force or total force production in the acceleration phase, raising the question of increased use of horizontal force production exercises to improve overall sprinting performance. This project received the top prize in the coaching category of the 2012 European Athletics Innovation Awards.